Experimental and Numerical Investigation of the Effect of Bypass Injection on Wall Temperature Distribution of a Single-Phase Mini/Micro-Channel. Issue 2 (24th December 2021) - Loganathan, Raamkumar; Mohiuddin, Ahmed; Gedupudi, Sateesh
Abstract: Temperature uniformity is an important factor in the thermal management of electronic devices. The present study investigates the effect of bypass injection on the wall temperature distribution of a single-phase mini/micro-channel using water as the coolant. Experimental studies were conducted on an 18 mm thick copper substrate heated by a cartridge heater, with the bypass inlet located midway between the channel inlet and outlet. After validating the numerical results with the experimental data, simulations were carried out on a 1 mm thin copper and silicon substrates with uniform and non-uniform heat flux conditions on the back of the substrate, for two different locations of bypass injection. Results for the thin copper and silicon substrates with uniform heat flux condition indicate that the bypass injection helps in reducing the difference between the maximum and minimum local wall temperatures by up to 60% and 76% for silicon and copper substrates, respectively. The reduction is higher for the bypass injection located midway between the channel inlet and outlet compared to the injection located at one-fourth of the channel length from the inlet. Bypass injection is found to be beneficial for the non-uniform (step change) heat flux condition, with the higher heat flux over the second half of the channel length. The experimental and numerical results for the thick copper substrate show a near-uniform wall temperature distribution even without bypass injection.